PRESENTATION LATIN AMERICAN GUITAR MUSIC BY UKRAINIAN PERFORMERS - Stanislav Zhovnir (International Journal of Innovative Technologies in Social Science, 2020)
The relevance of the study is determined by the need to study the influence of ethno-artistic (in particular, Latin American) traditions on the development of classical guitar art in the interaction of composing and performing. The general trends in the development of the creativity of Latin American composers for the guitar as an integral part of the Ibero-American music of the XX century are identified in the article. A general genre and style analysis of guitar works by Latin American composers A. Barrios, L. Brauer, E. Villa-Lobos, J. Morel, A. Piazzolla, J. Sagreras and others is presented. The author has analyzed the modern performing practice of representing this direction of guitar music in Ukraine. Examples of sound recordings are presented and a brief analysis of different genres of works by Latin American composers performed by Ukrainian classical guitarists A. Ostapenko, I. Fedorishin, A. Chadai-Fedik, D. Rybalchenko, B. Sidorenko, M. Zemlyansky, D. Buchka, V. Petrenko, V. Dotsenko, B. Belsky, M. Topchy is given. The performing models of creativity of Ukrainian guitarists in concert performing of Latin American works are determined. The article uses historical, cultural, systemic and comparative research methods, which is based on the analysis of the electronic portal "Guitarists and Composers", scientific works of V. Dotsenko, N. Kryazhev, V. Machneva.